2007
DOI: 10.1111/j.1095-8649.2007.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

The trophic ecology of Atlantic cod: insights from tri‐monthly, localized scales of sampling

Abstract: The meso-scale trophic dynamics of cod Gadus morhua were examined based upon tri-monthly stomach sample collections from a nearshore, localized (c. 800 km 2 ) region off Cape Cod, Massachusetts, U.S.A. The major objective for this work was to relate any changes in cod diet and amount of food eaten to seasonal variations in prey availability, water temperature and spawning at a spatial scale between broad-scale and laboratory studies. Results suggested that the type and amount of food eaten by cod was generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…McDermott et al (2015) used trawl gear in 2010-2011 in the Midcoast region to address similar questions regarding river herring as groundfish prey, finding that the odds of encountering river herring in groundfish stomachs was highest closest to the rivers where river herring spawn. Smith et al (2007) noted a similar seasonal pulse pattern of fish prey in cod diets.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…McDermott et al (2015) used trawl gear in 2010-2011 in the Midcoast region to address similar questions regarding river herring as groundfish prey, finding that the odds of encountering river herring in groundfish stomachs was highest closest to the rivers where river herring spawn. Smith et al (2007) noted a similar seasonal pulse pattern of fish prey in cod diets.…”
Section: Discussionmentioning
confidence: 64%
“…Stomach content analysis of groundfish from the Gulf of Maine (Garrison and Link 2000;Link et al 2009;Smith et al 2007) and nearshore waters of Midcoast Maine (McDermott et al 2015) have identified river herring as likely important to groundfish feeding behavior. These authors and others (Lake et al 2012;Saunders et al 2006) make strong and compelling arguments for restoring anadromous fish spawning habitat, particularly through dam removal, as a means of altering the decline of groundfish species.…”
Section: Introductionmentioning
confidence: 99%
“…Tagging studies have used angling techniques with feather hooks and jigs to capture spawning Atlantic Cod (e.g., Robichaud and Rose 2003;Dean et al 2012), which is indicative of a response to foraging stimuli. Feeding by spawning Atlantic Cod can also be greater than nonspawning fish or juveniles in some instances (Krumsick and Rose 2012) but appears to be more opportunistic because feeding has been observed to be more extensive postspawning (Link and Burnett 2001;Smith et al 2007).…”
Section: Behavior On the Spawning Sitementioning
confidence: 99%
“…As a generalist feeder, it is not unreasonable to infer that G . morhua might consume alosine prey when encountered (Link & Garrison, ; Smith et al , ; Link et al , ). Ames & Lichter () further hypothesize that G .…”
Section: Introductionmentioning
confidence: 99%